FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA KARYAWAN PT PUL LOGISTICS INDONESIA - Muhammad Syafei; Idqan Fahmi; Aida Vitayala S. Hubeis (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
The purposes of this study are 1) to analyzing the employee perceptions on the organizational culture, motivation, leadership, and work environment, and their effects on the employee performance of PT Pul Logistics Indonesia (PLI); 2) to analyze the most influential factors among the organizational culture, motivation, leadership, and work environment on the performance of PLI employees; 3) to formulate strategies to improve the performance of PLI employees by developing the organizational culture, motivation, leadership, and work environment. The methods utilized in this study were the Scale Analysis and Structural Equation Modeling (SEM). Thus, the organizational culture, motivation, leadership, and work environment have significant effects on the employee performance. Leadership is identified as the most influential factor followed by motivation, work environment, and organizational culture as the least. The formulation of strategies to improve employee performance covers the strengthening of professionalism culture, improvement in the commitment of performance assessment transparency, increase in knowledge and leadership awareness indicators, provision of supporting facilities and infrastructure, and increase in the understanding of employee SOP.Keywords: organizational culture, motivation, leadership, work environment, employee performance, SEMABSTRAKTujuan dari penelitian ini adalah 1) menganalisis persepsi karyawan terhadap budaya organisasi, motivasi, kepemimpinan dan lingkungan kerja, serta pengaruhnya terhadap kinerja karyawan PT Pul Logistics Indonesia (PLI); 2) menganalisis faktor yang paling berpengaruh di antara budaya organisasi, motivasi kerja, kepemimpinan, lingkungan kerja terhadap kinerja karyawan PLI; 3) merumuskan strategi meningkatkan kinerja karyawan PLI melalui peningkatan budaya organisasi, motivasi kerja, kepemimpinan, dan lingkungan kerja. Metode yang digunakan untuk menjawab tujuan adalah dengan analisis rentang skala dan analisis Structural Equation Modeling (SEM). Budaya organisasi, motivasi kerja, kepemimpinan dan lingkungan kerja memiliki pengaruh yang signifikan terhadap kinerja. Kepemimpinan merupakan faktor yang paling berpengaruh terhadap kinerja diikuti motivasi selanjutnya lingkungan kerja dan terakhir budaya organisasi. Rumusan strategi meningkatkan kinerja karyawan diantaranya penguatan budaya profesionalisme, peningkatan komitmen transparansi penilaian kinerja, peningkatan indikator pengetahuan dan kesadaran kepemimpin, pemenuhan sarana dan prasarana penunjang kerja, peningkatan pemahaman SOP karyawan. Kata kunci: budaya organisasi, motivasi, kepemimpinan, lingkungan kerja, kinerja karyawan, SEM